Astrology and Science: A Precarious Relationship. Part 2: Considerations of Empirical Investigations on the Validity of Astrology - Mayer, Gerhard A. (Journal of Scientific Exploration, 2020)
In Part 2 of “Astrology and Science: A Precarious Relationship”, the results of a population survey are first presented to reveal definitory problems in determining astrology. When investigating "astrology", of crucial importance are which concepts and practices to include. After definitional clarification, the anomalistic aspects of astrology or astrological practice are attended to with a distinction made between the above-below-theorem as the traditional basic assumption of astrology and possible psi phenomena that can occur in astrological counseling practice. Further sections describe problems in scientific studies on the validity of astrology. Such problems could have led to the failure of these efforts. Furthermore, specific methodological problems in the investigation of the above-below-theorem and in matching tests are addressed. In a final step, various scientific approaches to astrology are listed with their respective specific questions, methodological approaches and relevance for the scientific world view or astrological practice.